PENGARUH STARTEGI PEMBELAJARAN INDEX CARD MATCH TERHADAP HASIL BELAJAR POKOK BAHASAN BANGUN DATAR SISWA KELAS V MI AL-FALAH DAKIRING - Yuliana Alfiyatin; Moh. Amiril Mukminin (AL - IBRAH, 2023)
Based on the observation results at MI Al-Falah Dakiring, specifically in grade V, it shows that the learning process is still teacher-centered. Students are not given the opportunity to actively participate, especially in groups, making the learning atmosphere still felt boring, particularly in the subject of mathematics, which is associated with abstract material and is considered difficult to understand. This can be seen from the students' exam results, which are still below the Minimum Passing Criteria (KKM) of 70, and classically, it is observed that less than 80% of students achieve the expected grades. In the innovation of the learning process, the researcher wants to implement a different and more engaging teaching method to create a more enjoyable learning atmosphere. Students will be actively involved in the form of enjoyable games so that learning outcomes can be achieved as formulated. One alternative that can be developed to address this issue is through the implementation of the index card match learning strategy. It is hoped that this will create a new atmosphere that encourages students to actively participate in groups, allowing them to find answers through enjoyable exercises and interact well within study groups. The learning process becomes more interactive, allowing learning outcomes and objectives to be maximized. The subjects used in this study are 18 students. From the questionnaire results, 83.33% of students chose the answer "yes," and 91.7% of students scored above the KKM. The results of the hypothesis test analysis show that the calculated r=0.873, and the tabled r at a 5% significance level is 0.468. Therefore, it can be concluded that there is an influence of the index card match learning strategy on student learning outcomes in the topic of plane geometry in grade V at MI Al-Falah Dakiring.